Vector space modelling-based intelligent binary image encryption for secure communication. (19th May 2022) - Dankan Gowda, V.; Sharma, Avinash; Nagabushanam, M.; Govardhana Reddy, H. G.; Raghavendra, K.
Abstract: In this research work, a secured routing technique is developed based on the LEACH algorithm. Many secure routing algorithms were proposed in the past by modifying the LEACH algorithm with trust management techniques, key generation, and distribution technique and intrusion detection algorithms. Most present solutions are unable to address the issue of modifying and intercepting assaults. To tackle this problem, a new secured routing algorithm is developed in this work that divides the image and messages into sub-components, represent them in a matrix format and add them to get a steganographic image which is encrypted using a suitable encryption algorithm selected by the rule system developed in this research work. Moreover, intelligent agents are incorporated in all the sensor nodes in the network to communicate the encrypted images to the neighbor nodes more reliably.